Kearifan Lokal: Respon Masyarakat Minang terhadap Penjualan Rendang Non-Halal - Husen, Fathurrohman; Moh. Taufik; Sari Mustika (JURNAL AGROINDUSTRI HALAL, 2024)
Padang restaurants are synonymous with providing halal food. Padang Restaurant’s rejection of selling pork rendang is a strong background for this research. Padang customs are based on ABS-SBK (Basandi Syara-Syara Basandi Kitabullah Adat). This study aims to describe and analyze the response of the Minang community to a Padang restaurant that sells pork rendang. This research uses mixed methods. Quantitative techniques to collect primary data through questionnaires, and qualitative-descriptive techniques to collect secondary data and its analysis. Secondary data comes from news stories, journals, and scientific research results. Respondents’ answers about the identity and opinions of Padang Restaurants that sell non-halal products are arranged in the form of a Likert scale. Respondents were Minang people totaling 75 people. Respondents strongly disagreed that a Padang Restaurant sells pork rendang, even though the Padang Restaurant includes information on the non-halal product. The reason for refusing the sale of rendang using pork, aside from being identical to Minang, which has the ABS-SBK principle, is also due to the use of Minang attributes. The Minang people still hold tightly to their customs which make Islamic teachings part of their values, including in terms of food. The researcher suggests conducting research related to the need for regulation on the inclusion of the Padang Restaurant label which is synonymous with halal food products.